2004
DOI: 10.1111/j.1440-1843.2003.00526.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of antioxidants on exercise‐induced lipid peroxidation in patients with COPD

Abstract: Antioxidant levels were significantly lower in COPD patients than in control subjects. In these patients, exercise results in more significant oxidative stress and lipid peroxidation than in control subjects and antioxidant therapy may decrease lipid peroxidation following exercise and improve exercise capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 16 publications
4
20
1
Order By: Relevance
“…Increased oxidative stress has also been reported in COPD patients following both acute maximal7,8,10,41 and submaximal7,10 aerobic exercise. This has been the case with one exception,42 evident by reported increases in MDA,8,10 thiobarbituric acid-reactive substances (TBARS),7,41 protein oxidation (protein carbonyls),41 DNA damage (comet assay),10 phagocytic superoxide production,7,41 as well as changes in glutathione redox status7 and other components of the antioxidant defense system (e.g., total antioxidant status) 7.…”
Section: Acute Exercise-induced Oxidative Stress and Diseasementioning
confidence: 89%
“…Increased oxidative stress has also been reported in COPD patients following both acute maximal7,8,10,41 and submaximal7,10 aerobic exercise. This has been the case with one exception,42 evident by reported increases in MDA,8,10 thiobarbituric acid-reactive substances (TBARS),7,41 protein oxidation (protein carbonyls),41 DNA damage (comet assay),10 phagocytic superoxide production,7,41 as well as changes in glutathione redox status7 and other components of the antioxidant defense system (e.g., total antioxidant status) 7.…”
Section: Acute Exercise-induced Oxidative Stress and Diseasementioning
confidence: 89%
“…However, several studies have suggested that acute exercise may increase oxidative stress (OS), such as the increase in plasma thiobarbituric acid-reactive substance (TBARS) in COPD patients (Heunks et al 1999;Couillard et al 2002;Agacdiken et al 2004). In addition, Pinho et al (2007) reported that chronic exercise training can induce OS at baseline in COPD patients, and Barreiro et al (2009) demonstrated that nitrosative stress in severe COPD had increased after chronic endurance exercise.…”
Section: Introductionmentioning
confidence: 99%
“…The total antioxidative potential of the plasma reflects the ability of an individual to resist the oxidative stress. Ferric reducing ability of plasma (FRAP) evaluates plasma total antioxidant capacity due to known and unknown antioxidants in the plasma 10 Therefore in the present study significant reduction observed in total ferric reducing ability of plasma may be due to increased free radical activity either because of inflammation or complications that results in imbalance between antioxidant capacity and proxidant affecting lung function. Extensively amplified oxidant burden and declined individual antioxidant levels might be responsible for the observed significant fall in total antioxidant capacity of patients with lung disease.…”
Section: Aimsmentioning
confidence: 78%